Dampak Media Sosial Terhadap Kesehatan Mental Remaja di Era Digital - Siti Umairah; M. Fahli Zatrahadi; Miftahuddin Miftahuddin (AflahConsilia : Jurnal Bimbingan dan Konseling, 2026)
This study aims to examine how the use of social media impacts adolescent mental health in the digital era. The research employed a qualitative descriptive method with a phenomenological approach. Data were collected through open-ended online questionnaires distributed to school-aged adolescents aged 13 to 18 years who are active users of social media. The Colaizzi method was utilized to identify emerging themes from the participants' experiences. Data collection techniques included observation and in-depth interviews, and the data were analyzed using the following steps: data reduction, data display (presentation), and conclusion drawing/verification. The findings revealed three main conclusions. First, when adolescents' posts did not receive the expected social responses, many experienced disappointment, sadness, and diminished self-esteem, indicating that social validation significantly influences their emotional well-being. Second, excessive use of social media was found to have adverse effects on both mental and physical health, manifesting as anxiety, overthinking, and a tendency toward unfavorable social comparison. Third, social media was shown to exacerbate negative emotions and undermine adolescents' self-confidence. This study suggests that social media exerts a complex influence on adolescent mental health. Consequently, enhanced digital literacy, active involvement from parents and educators, and adequate psychological support are essential to enable adolescents to engage with social media in a safe, healthy, and responsible manner.